(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Communication basically is important thing For guard harmony family. Ability member family For endure life will depends on ability they For communicate. Virginia Satir describes communication the good one as open, clear , honest and harmonious communication. Draft i -message from Virginia Satir believed capable build congruent interpersonal communication (in family). Application communication this is very correct applied to the type family consensual that is family Which own conformity And conversation Which high. Application i-good message in family consensual will give birth to resilience a strong family , that is resilient family to threat external. Method used in study This is studies case with approach qualitative. Paradigm communication Which used is postpositivist with tradition sociopsychological . Informant in study This is family consensual. Test validity data use triangulation source . Results study show that application of 5 i -message formulas consisting of from: sensing , emotion, want, behavior, and effect in communication family consensual cause interaction and communication more intensive so that resilience family formed with strong.